The story of transformation" in Kashf-ol-Asrar va Odat ol-Abrar - Leila Pazhoohandeh; Maryam Sadat Dastgeib (ادبیات عرفانی)
In some Sufi stories, we encounter the transformation of one of the characters; however, we typically expect to see static characters in these narratives. In such cases, when a character undergoes transformation, they become the focal point of the story. Some of these transformations occur suddenly, as a result of dignity or miracles, while others unfold logically and causally. There are 37 stories in total, spanning the first to tenth volumes of Kashf-ol-Asrar va Odat ol-Abrar Meibodi. The main focus of this research, in addition to identifying the reasons and origin of the transformation; is to examine how revelation and inner transformation are reflected in the structure of the narrative. This analysis is conducted in a descriptive and analytical manner, supported by tables. The results of the research are examples of relative verisimilitude, the empathy of the audience with the story, the weak presence of women in the story of transformation, the necessity of background and inner talent, transformation in a positive direction, the permanence of experience, returning to God as the general meaning of stories. It shows techniques such as the use of more complex plots, first-person or combined perspective, and dealing with the details of characters' situations. It can be said that "the story of transformation" or "growth and perfection" not only provides a suitable platform for innovation in narrative elements but also clarifies the author’s intellectual framework. By elucidating the concept of transformation, along with literary and artistic influences and dominant discourses, it allows for a more comprehensive understanding of the interpretation.